INNV-16. CNS-TAP TOOL RECOMMENDATIONS OF TARGETED ANTI-CANCER AGENTS COMPARED TO THOSE SELECTED BY A MULTIDISCIPLINARY TUMOR BOARD IN A MOLECULARLY-DRIVEN DIPG CLINICAL TRIAL (PNOC003). (12th November 2021) - Roberts, Holly; Ravi, Karthik; Schepers, Allison; Marini, Bernard; Kline, Cassie; Mueller, Sabine; Koschmann, Carl; Franson, Andrea
Abstract: Genetic sequencing of diffuse intrinsic pontine gliomas (DIPG) has revealed genomic heterogeneity, sparking an interest in individualized and targeted treatment options for this particularly devastating disease. A feasibility study, PNOC003: Molecular Profiling for Individualized Treatment Plan for DIPG (NCT02274987), was completed within the Pacific Pediatric Neuro-Oncology Consortium. In this study, a multidisciplinary tumor board reviewed detailed molecular and genomic profiling of each participant's tumor and made molecularly-targeted treatment recommendations. Separately, our team developed the Central Nervous System Targeted Agent Prediction (CNS-TAP) tool, which combines pre-clinical, clinical, and CNS penetration data with patient-specific genomic information to derive numeric scores for targeted anticancer agents, aimed to objectively evaluate these therapies for use in patients with CNS tumors. We hypothesized that highly-scored agents within CNS-TAP would overlap with the agents recommended by the tumor board in PNOC003. For each study participant, we used the genomic profiling report to identify actionable alterations and incorporated these data into CNS-TAP to identify the highest-scoring agents. We compared high-scoring agents within CNS-TAP with recommendations from the tumor board for each of the enrolled 28 participants. Overall, 93% of patients (26/28) had at least one agent recommended by both the tumor board and CNS-TAP. Additionally, 38% of all agents (36/95) recommended by the tumor board were also selected by CNS-TAP. We identified factors that likely contributed to the differences in therapy recommendations between these two methods: CNS-TAP requires additional clinician input to account for drug-drug interactions, includes only classically-defined anticancer agents, and cannot easily be updated in real-time as new data emerge. However, CNS-TAP provides an objective evaluation of targeted therapies, whereas tumor boards are inherently subjective. A prospective study incorporating both CNS-TAP and a molecular tumor board for targeted therapy selection in high-grade glioma is currently ongoing to further compare and objectively evaluate these methods.